2009
DOI: 10.1021/ol9009128
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of (+)-19-Deoxyicetexone, (−)-Icetexone, and (+)-5-Epi-icetexone

Abstract: The first asymmetric total syntheses of 19-deoxyicetexone, icetexone, and 5-epi-icetexone was achieved from epimeric tricyclic dienes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…Majetich and Grove completed the first enantioselective syntheses of icetexone, epi -icetexone, and 19-deoxyicetexone in 2009 using a ‘cyclialkylation’ strategy to form the [6-7-6] tricyclic core. 7 As noted above, the Majetich synthesis led to reassignment of the spectral data reported in the literature for both icetexone and epi -icetexone. In 2010, we reported formal syntheses of racemic icetexone and epi -icetexone.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Majetich and Grove completed the first enantioselective syntheses of icetexone, epi -icetexone, and 19-deoxyicetexone in 2009 using a ‘cyclialkylation’ strategy to form the [6-7-6] tricyclic core. 7 As noted above, the Majetich synthesis led to reassignment of the spectral data reported in the literature for both icetexone and epi -icetexone. In 2010, we reported formal syntheses of racemic icetexone and epi -icetexone.…”
Section: Introductionmentioning
confidence: 80%
“…6 Of note, in the account pertaining to the biological activity of 2 , Sanchez et al reported the spectral data for isolated epi -icetexone, which matches the data for synthetic icetexone (and not synthetic epi -icetexone) reported by Majetich. 7 As such, the Nieto et al report on the isolation of these compounds may have switched the assignment of the two structures and therefore the reported biological activity for epi -icetexone may in fact be that of icetexone.…”
Section: Introductionmentioning
confidence: 99%
“…It was accompanied by substantial amounts of methyl ether 28 (a side product previously reported in these reactions) and, to our surprise, cyclobutane 29 . The latter results from a rare 4‐ exo ‐trig radical cyclization, which generates a secondary radical . This unusual selectivity presumably results from the constrained nature of the caged precursor.…”
Section: Methodsmentioning
confidence: 99%
“…The latter results from a rare 4-exo-trig radical cyclization, which generates a secondary radical. [37] This unusual selectivity presumably results from the constrained nature of the caged precursor. Increasing the concentration of tributyl tin hydride suppressed this cyclization but also led to higher yields of the unwanted methyl ether 28.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…The subsequent conversion of 8 to quinone (±)-2 required seven additional steps and occurred in 52% overall yield (Scheme 3). The use of 1,2,4-trimethoxybenzene (9) [44,45] or carvacrol (10) as the starting material [46] to prepare bromide 8 required fewer steps and gave better overall yield, without the isolation or purification of any intermediates. Since the C-5 chiral center in quinone 2 controls the stereochemistry for each new chiral center produced in the tandem polycyclizations leading to (+)-perovskone, the preparation of quinone 2 in optically active form was essential to prepare (+)-perovskone.…”
Section: F-ring Formationmentioning
confidence: 99%